KEDUDUKAN ORGANISASI ADVOKAT SEBAGAI WADAH TUNGGAL PROFESI PASCA PUTUSAN MAHKAMAH KONSTITUSI - Muhammad Fajar Sidiq Widodo; Sudarsono Sudarsono; Bambang Winarno (Universitas Negeri Malang, 2018)
Advocate is a free and independent profession. According to the Constitutional Court Decision number 112/PUU–XII/2014 & 36/PUU–XIII/2015. It is interesting that the decision has decided the issue of oath in Article 4 Paragraph (1) Advocate Law, but affects Article 28 Paragraph (1) concerning Advocates Organization. This research is a normative research that uses conceptual approach and legislative approach, which hopefully can dig up and find out the position of Advo- cates Organizations after the Constitutional Court Decision number 112/PUU–XII/2014 & 36/PUU– XIII/2015. It is known from the research that the Constitutional Court is unauthorized to decide which organization is legitimate, although Advocates Organization can also be named as state institution.